Highly Efficient Synthesis of 1-Thioamidoalkyl-2-naphthols and 14-Aryl-14H-dibenzo[a,j]xanthenes using a Novel Ionic Liquid: Catalyst Preparation, Characterization and Performing the Reactions - Atefeh Saadat; Abdolkarim Zare; Fatemeh Jamadi; Maasoomeh Abdolalipour-Saretoli (Department of Chemical Engineering - Diponegoro University, 2018)
In this work, a novel Brønsted acidic ionic liquid namely triethylaminium-N-sulfonic acid trifluoroacetate [TEASA][TFA] has been synthesized by the reaction of NEt3 with ClSO3H, and then with CF3CO2H. The ionic liquid has been characterized by studying its spectroscopic data (1H and 13C NMR, FT-IR, and mass spectra). Afterward, it has been utilized as a highly effective and general catalyst to promote the following organic reactions in solvent-free conditions: (i) the production of 1-thioamidoalkyl-2-naphthols from arylaldehydes, 2-naphthol and thioacetamide, and (ii) the preparation of 14-aryl-14H-dibenzo[a,j]xanthenes from arylaldehydes and 2-naphthol. It is noteworthy that [TEASA][TFA] has catalyzed the reactions under milder conditions relative to most of the reported methods. Moreover, it afforded the both products in higher yields with respect to most of the previous works.